The never-ending pursuit of a definitive chemical classification system for granites - Garcia-Arias,M. (Journal of Geosciences, 2020)
Chemical classifications of granites sensu lato have been developed and revisited over decades, but no classification scheme has been universally accepted yet. The more or less known coupled reasons for this apparently impossible task are reviewed here. The main problem is that different granitoids do not fall in distinct categories with sharp boundaries, but comprise a continuous spectrum of rock types both in their chemical and modal compositions. The unifying factor is the minimum-melt nature of the granites sensu stricto, as primary and evolved melts can have a granitic composition. This minimum-melt nature has two consequences, which are the main reasons for the absence of sharp boundaries in every compositional classification system, either modal or chemical. Firstly, the chemistry of granites spreads from the minimum melt to non-minimum compositions, and thus some granites represent a rock series formed by a continuous magmatic evolution, not by discrete steps; secondly, granite series, which are generated from different sources and by several petrogenetic processes, eventually converge at the most silica-rich compositions. There is a relationship between the tectonic scenarios of formation of granites and the chemical overlap that contributes to the absence of a satisfactory chemical classification: the protracted evolution of the tectonic settings following the Wilson cycle and more compli¬cated scenarios change the chemical and modal composition of the granite sources. The overlap in the most silica-rich compositions of the granites s.l. due to the minimum melt nature may extend to more mafic members in a granite series: the closer the sources are in their composition, the greater is the overlap, becoming a second contribution to the lack of sharp boundaries between granite types.The huge efforts to create a satisfactory chemical compositional classification system have actually led to a significant contribution to granite petrology: the discovery of the main chemical differences between granite types, the main chemical parameters (silica content, alkalinity, aluminosity, maficity or FeOt + MgO content, and the Fe/Mg and Na/K ratios) and the petrogenetic processes that cause the change in these parameters. Therefore, despite the lack of agreement over the ’perfect’ classification system, the investigations have not been fruitless: they have led to the realization that non-genetic classifications are preferable to name the individual rock samples; chemical classification schemes should be left to distinguish magmatic suites and to unravel their prospective petrogenesis and geotectonic setting.
Keywords: granites; chemical classifications; tectonic settings; magmatic evolution; petrogenesis